2002
DOI: 10.1046/j.1365-2486.2002.00464.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal respiration of foliage, fine roots, and woody tissues in relation to growth, tissue N, and photosynthesis

Abstract: Autotrophic respiration may regulate how ecosystem productivity responds to changes in temperature, atmospheric [CO2] and N deposition. Estimates of autotrophic respiration are difficult for forest ecosystems, because of the large amount of biomass, different metabolic rates among tissues, and seasonal variation in respiration rates. We examined spatial and seasonal patterns in autotrophic respiration in a Pinus strobus ecosystem, and hypothesized that seasonal patterns in respiration rates at a common tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
113
4
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(136 citation statements)
references
References 55 publications
(114 reference statements)
17
113
4
2
Order By: Relevance
“…For example, Vose and Ryan (2002) showed empirically that maintenance respiration rates vary nearly 40-fold among the different tissues of Pines strobus tissues, whereas Lavigne and Ryan (1997) reported lower stem maintenance respiration rates in the angiosperms vs. the gymnosperms among their study species. Furthermore, our data indicate that conifers have lower scaling exponents for leaf biomass with respect to either stem or root biomass compared to angiosperms ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Vose and Ryan (2002) showed empirically that maintenance respiration rates vary nearly 40-fold among the different tissues of Pines strobus tissues, whereas Lavigne and Ryan (1997) reported lower stem maintenance respiration rates in the angiosperms vs. the gymnosperms among their study species. Furthermore, our data indicate that conifers have lower scaling exponents for leaf biomass with respect to either stem or root biomass compared to angiosperms ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Scaling relationship n α 95% CI log β r 2 F * P * ( Hikosaka, 2003( Hikosaka, , 2005Lusk et al, 2003 ;Ryan et al, 1994 ;Lavigne and Ryan, 1997 ;Vose and Ryan, 2002 ;Zha et al, 2004 ;Koyama and Kikuzawa, 2009 ;Reich et al, 2008 ;Lusk, 2011 ), and that the accumulation of dead tissues in woody organs can affect respiration scaling relationships Niklas, 2011 , 2012 ). For example, Vose and Ryan (2002) showed empirically that maintenance respiration rates vary nearly 40-fold among the different tissues of Pines strobus tissues, whereas Lavigne and Ryan (1997) reported lower stem maintenance respiration rates in the angiosperms vs. the gymnosperms among their study species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryan et al (1996) demonstrated that efflux of CO 2 from fine roots was linearly related to root N content in Pinus radiata in Australia. Vose and Ryan (2002) found that a significant correlation existed between coarse root respiration and root N content in a white pine forest in USA. Sun et al (2004) and Chen et al (2008) both observed a positive correlation between wheat root respiration coefficient and root N content.…”
Section: Resultsmentioning
confidence: 98%
“…Respiration, especially maintenance respiration, has been linked with tissue N content (Ryan 1991) Bouma et al 1994), and because other maintenance process such as ion transport may be correlated with protein content (Vose and Ryan 2002). Ryan et al (1996) demonstrated that efflux of CO 2 from fine roots was linearly related to root N content in Pinus radiata in Australia.…”
Section: Resultsmentioning
confidence: 99%